2022
DOI: 10.3390/su14031820
|View full text |Cite
|
Sign up to set email alerts
|

The Oil Palm Governance: Challenges of Sustainability Policy in Indonesia

Abstract: Nowadays, Indonesian palm oil faces agrarian, environmental, and social issues and has been subject to sharp criticism from the international community for many years. To answer this problem, the Indonesian government implemented a strategy through certification which ensured the achievement of sustainability standards, especially on the upstream side of the palm oil supply chain. The implementation of Indonesian Sustainable Palm Oil (ISPO) was an ultimate instrument that applied in particular to smallholders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 58 publications
0
25
0
6
Order By: Relevance
“…Regarding the sustainability criteria, the ISPO standard is rather diversified in comparison to the RED or RenovaBio. It comprises a broader range of principles, including social ones, even though the implementation of the ISPO remains rather weak so far (see, e.g., Hidayat et al 2018;Choiruzzad et al 2021;Putri et al 2022). In terms of global trade, however, the broad scope of the criteria is not supposed to be an obstacle, but rather quite the opposite.…”
Section: Ispo In Indonesia: Sustainability As a Tool Of National Sove...mentioning
confidence: 99%
“…Regarding the sustainability criteria, the ISPO standard is rather diversified in comparison to the RED or RenovaBio. It comprises a broader range of principles, including social ones, even though the implementation of the ISPO remains rather weak so far (see, e.g., Hidayat et al 2018;Choiruzzad et al 2021;Putri et al 2022). In terms of global trade, however, the broad scope of the criteria is not supposed to be an obstacle, but rather quite the opposite.…”
Section: Ispo In Indonesia: Sustainability As a Tool Of National Sove...mentioning
confidence: 99%
“…al [20], found that the European food industry is currently requesting the Roundtable on Sustainable Palm Oil (RSPO) standard, while the European biodiesel industry is seeking International Sustainability and Carbon Certification (ISCC) [20]. Therefore, the Government of Indonesia requires large-scale and small-scale plantation companies to have Indonesian Sustainable Palm Oil (ISPO), where this certification is expected to be a ticket for plantation companies or self-help groups to remain productive without ignoring environmental and social issues in the palm oil industry national and local [21,22]. In addition, the solution that can be taken to overcome the problem of oil palm development is a collaboration between companies that act as the nucleus, and oil palm smallholders as plasma to consistently apply the principles of sustainability.…”
Section: Figure 1 the Problems Of Oil Palm Development In Riau Provincementioning
confidence: 99%
“…Through this policy, support for oil palm development includes rejuvenation activities, human resource development, as well as facilities and infrastructure assistance. This activity integrates all aspects of oil palm plantation development to increase the productivity of smallholders [12,22].…”
Section: Sustainable Oil Palm Plantationmentioning
confidence: 99%
“…Oil palm producers usually refuse to replant their old oil palm trees because they still produce yield and provide income (Putri et al, 2022). This situation has led to many old palm oil areas still being left to grow, although the oil palm has shown a decrease in yielding.…”
Section: Literature Reviewmentioning
confidence: 99%